The Changing Benefits of Early Work Experience - Charles L. Baum; Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2014)
We examine whether the benefits of high school work experience have changed over the last 20 years by comparing effects for the 1979 and 1997 cohorts of the National Longitudinal Survey of Youth. Our main specifications suggest that the future wage benefits of working 20 hours per week in the senior year of high school have fallen from 8.3 percent for the earlier cohort, measured in 1987-1989, to 4.4 percent for the later one, in 2008-2010. Moreover, the gains of work are largely restricted to women and have diminished over time for them. We are able to explain about five-eighths of the differential between cohorts, with most of this being attributed to the way that high school employment is related to subsequent adult work experience and occupational attainment.
Keywords: J13; J24; J31; 330; youth employment; work experience; wages